THE CHALLENGES ASSOCIATED WITH INSTRUCTING ENGLISH FOR SPECIFIC PURPOSES (ESP) TO MIDWIFERY STUDENTS: - Yuliana Yuliana; Annisa Astrid; Deta Desvitasari (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
The challenges encountered by instructors while delivering English for Specific Purposes (ESP) instruction to midwifery students enrolled at STIKES Abdurahman Palembang, Indonesia. The research methodology utilized in this investigation was qualitative in nature, employing a case study approach. The present investigation involved a purposive sampling technique to select two English for Specific Purposes (ESP) instructors who teach D3 Midwifery students at STIKES Abdurahman Palembang as participants. The data were collected via interviews and subsequently analyzed and presented descriptively utilizing thematic analysis. The study's results revealed that instructors encountered various obstacles while teaching English for Specific Purposes (ESP). These challenges encompassed the following: a) Improving the proficiency of students in midwifery owing to inadequate knowledge, b) administering the classroom, and c) instructing English for Specific Purposes (ESP) in accordance with the institution's syllabus.